2017
DOI: 10.1159/000466706
|View full text |Cite
|
Sign up to set email alerts
|

Iron Status of Vegetarian Children: A Review of Literature

Abstract: Background: Iron is considered a nutrient of concern for vegetarians. In children, inadequate iron status may lead to anemia and poor growth. Summary: Thirteen original manuscripts met the inclusion criteria. Various biochemical markers of iron status, such as hemoglobin (Hb) and serum ferritin, were used. Seven of the 13 studies reported the prevalence of iron deficiency separately for vegetarians and non-vegetarians. Five out of 7 showed a higher prevalence of iron deficiency among the vegetarian participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 18 publications
(89 reference statements)
3
20
0
3
Order By: Relevance
“…At present, there is only limited evidence to substantiate this, most of which is from studies in adults. A review of vitamin B12 status among adolescent vegetarians reported a deficiency prevalence of 21–41% (based on methylmalonic acid concentration – one of several vitamin B12 status markers), based on two small‐scale studies where participants followed a macrobiotic diet until age 6 years, before switching to a lacto‐vegetarian (consume dairy only), lacto‐ovo vegetarian (consume dairy and eggs) or omnivorous diet (Pawlak & Bell 2013).…”
Section: What Is the Contribution Of Animal‐derived Foods In Healthy mentioning
confidence: 99%
“…At present, there is only limited evidence to substantiate this, most of which is from studies in adults. A review of vitamin B12 status among adolescent vegetarians reported a deficiency prevalence of 21–41% (based on methylmalonic acid concentration – one of several vitamin B12 status markers), based on two small‐scale studies where participants followed a macrobiotic diet until age 6 years, before switching to a lacto‐vegetarian (consume dairy only), lacto‐ovo vegetarian (consume dairy and eggs) or omnivorous diet (Pawlak & Bell 2013).…”
Section: What Is the Contribution Of Animal‐derived Foods In Healthy mentioning
confidence: 99%
“…Studienergebnisse zur Prävalenz eines Eisenmangels bei vegetarischer (inkl. vegane) Kinderernährung sind jedoch nicht eindeutig [30]. Eine Supplementie-rung von Eisen sollte erst nach Diagnose eines Eisenmangels erfolgen [31].…”
Section: Frühstückunclassified
“…Studies on vegetarians have generally shown them to be at much greater risk for iron deficiency. Although most studies show that vegetarians=vegans tend to have a similar or higher daily intake of iron compared with omnivores, the former tend to have significantly lower mean serum ferritin concentrations due to the lower bioavailability of iron in the vegetarian diet (see, e.g., Baines, Powers, and Brown 2007;Ball and Bartlett 1999;Pawlak and Bell 2017;Snyder, Dvorak, and Roepke 1989;Wilson and Ball 1999). Wilson and Ball (1999), for example, found that among Australian men, iron intake among vegetarians and vegans was 29-49%…”
Section: Soy and Other Legumesmentioning
confidence: 99%